Molecular sieve catalyst for isomerization of xylene and preparation method and application thereof

By combining aluminum-rich multi-stage porous hydrogen-type ZSM-48 molecular sieve with binder, the silicon-aluminum ratio and pore structure are solved, and the problems of insufficient diffusion performance and insufficient acid density in xylene isomerization reaction of ZSM-48 molecular sieve are solved. A catalyst with high selectivity and stability is achieved, simplifying the preparation process.

CN119158615APending Publication Date: 2024-12-20DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310730611.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The ZSM-48 molecular sieve has insufficient diffusion performance in xylene isomerization reaction, resulting in low catalytic stability and a high silicon-aluminum ratio leading to insufficient acid density, affecting catalytic activity.

Method used

The catalyst was prepared by a one-step hydrothermal crystallization method by combining aluminum-rich multi-stage pore hydrogen-type ZSM-48 molecular sieve and binder, and the silicon-aluminum ratio and pore structure were adjusted to improve the selectivity and stability of the catalyst.

Benefits of technology

The diffusion properties and catalytic activity of the catalyst are significantly improved, the selectivity and catalytic stability of paraxylene are improved, and the preparation process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004295907530000111
    Figure BDA0004295907530000111
  • Figure HDA0004295907540000011
    Figure HDA0004295907540000011
  • Figure HDA0004295907540000021
    Figure HDA0004295907540000021
Patent Text Reader

Abstract

The invention provides a xylene isomerization molecular sieve catalyst and a preparation method and application thereof. The catalyst is a catalytic material with a ZSM-48 molecular sieve as a main catalyst component. Wherein the ZSM-48 molecular sieve is synthesized by adopting proper raw materials, finely adjusting the molar composition of the raw materials, selecting proper seed crystals and adopting a one-step hydrothermal crystallization method. The molecular sieve material has a wide adjustable range of silica-alumina ratio (SiO2 / Al2O3, 40-200), relatively high mesoporous volume (0.20-0.80 cm < 3 > / g) and excellent diffusion performance. The catalyst obtained after the molecular sieve is subjected to tabletting molding or extrusion molding with a binder has good catalytic activity, excellent catalytic stability and p-xylene selectivity in xylene isomerization reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a xylene isomerization molecular sieve catalyst and a preparation method and application thereof, belonging to the technical field of catalytic chemistry. Background Art

[0002] As a monomer for producing p-dibenzoic acid and a variety of subsequent chemical products, the demand for p-xylene has been increasing in recent years. As a process for converting low-value-added mixed C8 aromatics into p-xylene-rich high-value-added products, xylene isomerization has become an important way to increase the production of p-xylene. This process is a typical acid-catalyzed process, and molecular sieve catalysts are the current mainstream catalytic materials. It not only provides the B acid active center required for the reaction, but also the shape-selective effect of its microporous channel system is indispensable for improving the selectivity of p-xylene and inhibiting the occurrence of side reactions. At present, the mainstream catalysts of this process are ZSM-5 molecular sieve (CN111744542A, CN100425343C), EU-1 molecular sieve (CN110548536A, CN110548536A) and MOR molecular sieve (CN110694681A, CN102060309A). In recent years, studies (Hyung-Ki Min; Seung Hyeok Cha; Suk Bong Hong, ACS catalysis, 2012, 2, 971-981) have shown that one-dimensional ten-membered ring pore molecular sieves exhibit better para-xylene selectivity in the isomerization reaction of meta-xylene, but the diffusion limitation brought by the one-dimensional pore system seriously weakens the catalytic stability of the one-dimensional pore molecular sieve.

[0003] ZSM-48 molecular sieve has a one-dimensional ten-membered ring channel along the

[100] direction. Its unique channel structure enables it to exhibit excellent shape selectivity in the xylene isomerization reaction. However, how to improve the diffusion performance of ZSM-48 molecular sieve and thus enhance its catalytic stability remains a challenge. In addition, the inherent high silicon-aluminum ratio of ZSM-48 molecular sieve leads to its insufficient acid density. How to reduce the silicon-aluminum ratio of ZSM-48 molecular sieve and thus improve the catalytic activity is also an important issue. Summary of the invention

[0004] The purpose of the present invention is to develop a catalytic material for xylene isomerization. The xylene isomerization catalyst obtained by the method has the characteristics of high selectivity for p-xylene, good catalytic activity and stability.

[0005] According to one aspect of the present application, a xylene isomerization molecular sieve catalyst is provided, wherein the xylene isomerization molecular sieve catalyst comprises an aluminum-rich multi-level pore hydrogen-type ZSM-48 molecular sieve having a short rod-like stacking morphology and a binder;

[0006] The mass content of the aluminum-rich multi-level pore hydrogen-type ZSM-48 molecular sieve in the xylene isomerization molecular sieve catalyst is 40 to 90 wt %;

[0007] Optionally, the mass content of the aluminum-rich multi-level porous hydrogen-type ZSM-48 molecular sieve in the xylene isomerization molecular sieve catalyst is any value of 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt% or any range value between two of them.

[0008] The silicon-aluminum ratio of the aluminum-rich multi-level pore hydrogen-type ZSM-48 molecular sieve is 400 to 200;

[0009] Optionally, the silicon-aluminum ratio of the aluminum-rich multi-level pore hydrogen-type ZSM-48 molecular sieve is any value among 200, 250, 300, 350, 400, or a range value between any two of them.

[0010] The micropore volume of the aluminum-rich multi-level pore hydrogen-type ZSM-48 molecular sieve is 0.04 to 0.09 cm 3 / g;

[0011] Optionally, the micropore volume of the aluminum-rich multi-level pore hydrogen-type ZSM-48 molecular sieve is 0.04 cm 3 / g, 0.05cm 3 / g, 0.06cm 3 / g, 0.07cm 3 / g, 0.08cm 3 / g, 0.09cm 3 / g, or any range of values ​​between them.

[0012] The mesopore volume of the aluminum-rich multi-level pore hydrogen-type ZSM-48 molecular sieve is 0.2 to 0.8 cm 3 / g;

[0013] Optionally, the mesopore volume of the aluminum-rich multi-level pore hydrogen-type ZSM-48 molecular sieve is 0.2 cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, or any range of values ​​between them.

[0014] The binder is selected from at least one of alumina, silica and clay.

[0015] According to another aspect of the present application, a method for preparing the above-mentioned xylene isomerization molecular sieve catalyst is provided, which solves the above-mentioned technical problem by using suitable raw materials, finely adjusting the molar composition of the raw materials, and using a one-step hydrothermal crystallization method, comprising the following steps:

[0016] The raw materials containing silicon source, aluminum source, inorganic base, template agent, seed crystal and water are placed in a sealed container for aging, crystallization, ion exchange, roasting and molding to obtain the xylene isomerization molecular sieve catalyst.

[0017] Furthermore, the method comprises the following steps: dissolving raw materials containing aluminum source, inorganic base and template agent in deionized water under stirring conditions, and then sequentially adding seed crystals and silicon source to carry out aging, crystallization and ion exchange processes.

[0018] The solid product obtained after the crystallization is filtered, washed and dried to obtain the molecular sieve raw powder.

[0019] The obtained molecular sieve raw powder is subjected to ammonium ion exchange and roasting to obtain a hydrogen-type molecular sieve catalyst. The ion exchange process is: add the molecular sieve raw powder to a 1 mol / L NH4Cl solution with a liquid-to-solid mass ratio of 6 to 30, and stir at 80°C for 1 hour. Repeat the exchange 3 times, filter, and wash to obtain an ammonium-type molecular sieve. The ammonium-type molecular sieve is calcined at 550°C in an air atmosphere for 4 hours to obtain a hydrogen-type ZSM-48 molecular sieve catalyst. The hydrogen-type ZSM-48 molecular sieve catalyst is formed into tablets or mixed with a binder and extruded to obtain the above-mentioned xylene isomerization molecular sieve catalyst.

[0020] The concentration of the ammonia water is 25wt%;

[0021] The silicon source is selected from at least one of white carbon black, silica sol, ethyl orthosilicate and water glass;

[0022] The aluminum source is selected from at least one of aluminum nitrate, aluminum sulfate, sodium aluminate, pseudo-boehmite, and aluminum chloride;

[0023] The inorganic base is selected from at least one of sodium hydroxide, sodium carbonate, potassium hydroxide, lithium hydroxide and ammonia water;

[0024] The template agent is at least one of hexamethylammonium bromide (HMBr), hexamethylammonium chloride (HMCl) and hexamethylammonium hydroxide (HMOH).

[0025] The molar ratio of the inorganic base to the silicon source is 0.2 to 0.6;

[0026] Optionally, the molar ratio of the inorganic base to the silicon source is any value among 0.2, 0.3, 0.4, 0.5, 0.6 or a range value between any two of them.

[0027] The molar ratio of the silicon source to the aluminum source is 60 to 250;

[0028] Optionally, the molar ratio of the silicon source to the aluminum source is any value among 60, 80, 100, 120, 140, 160, 180, 200, 220, 240, 250 or a range value between any two of them.

[0029] The molar ratio of the template to the silicon source is 0.02 to 0.3;

[0030] Optionally, the molar ratio of the template to the silicon source is any value among 0.02, 0.05, 0.1, 0.2, 0.3 or a range between any two of them.

[0031] The molar ratio of the water to the silicon source is 25 to 60;

[0032] Optionally, the molar ratio of the water to the silicon source is any value among 25, 30, 35, 40, 45, 50, 55, 60 or a range value between any two of them.

[0033] The mass ratio of the seed crystal to SiO2 in the silicon source is 1% to 20%;

[0034] Optionally, the mass ratio of the seed crystal to SiO2 in the silicon source is any value of 1%, 5%, 10%, 15%, 20%, or a range between any two of them.

[0035] The molar amount of the silicon source is calculated based on the molar amount of SiO2 in the selected silicon source;

[0036] The molar amount of the aluminum source is calculated based on the molar amount of Al2O3 in the selected aluminum source;

[0037] The molar amount of the template is calculated based on the molar amount of hexamethylammonium ions in the selected template;

[0038] The molar amount of the inorganic base is calculated based on the molar amount of the hydroxide in the selected inorganic base.

[0039] The aging temperature is 25 to 80° C.

[0040] Optionally, the aging temperature is any value of 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, or any range therebetween.

[0041] The aging time is 2 to 8 hours.

[0042] Optionally, the aging time is any value among 2h, 3h, 4h, 5h, 6h, 7h, 8h, or a range value between any two of them.

[0043] The crystallization temperature is 140-200°C.

[0044] Optionally, the crystallization temperature is any value of 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, or a range between any two of them.

[0045] The crystallization time is 12 to 120 hours.

[0046] Optionally, the crystallization time is any value among 12h, 24h, 36h, 48h, 60h, 72h, 84h, 96h, 108h, 120h or a range between any two of them.

[0047] The crystallization is hydrothermal dynamic crystallization, which is carried out in a kettle reactor in a rotary oven, and the rotating speed of the rotary oven is 10-80r / min.

[0048] The seed crystals are ZSM-48 seed crystals, which are made by the applicant.

[0049] The ZSM-48 seed crystals are obtained by the following process:

[0050] The raw materials containing silicon source I, aluminum source I, inorganic base I, template agent I, organic additive and water are aged I, crystallized I and dried in a closed container to obtain the ZSM-48 seed crystal;

[0051] The silicon source I is selected from at least one of white carbon black, silica sol, ethyl orthosilicate, and water glass;

[0052] The aluminum source I used is at least one of aluminum nitrate, aluminum sulfate, sodium aluminate, pseudo-boehmite, and aluminum chloride;

[0053] The template agent I is selected from 1,6-hexanediamine;

[0054] The inorganic base I is selected from at least one of sodium hydroxide, sodium carbonate, potassium hydroxide, lithium hydroxide and ammonia water;

[0055] The organic additive is selected from tetramethylammonium hydroxide (TMAOH), tetramethylammonium chloride

[0056] At least one of tetramethylammonium bromide (TMACl), tetramethylammonium bromide (TMABr), tetramethylammonium fluoride (TMAF), tetraethylammonium bromide (TEABr), tetraethylammonium chloride (TEACl), tetraethylammonium hydroxide (TEAOH), and tetraethylammonium fluoride (TEAF).

[0057] The molar ratio of the silicon source I to the aluminum source I is at least 200; that is, optionally, only the silicon source is contained;

[0058] The molar ratio of the inorganic base I to the silicon source I is 0.03 to 0.2;

[0059] Optionally, the molar ratio of the inorganic base I to the silicon source I is any value among 0.03, 0.05, 0.1, 0.15, 0.2, or a range between any two of them.

[0060] The molar ratio of the template agent I to the silicon source I is 0.2 to 0.6;

[0061] Optionally, the molar ratio of the template I to the silicon source I is any value among 0.2, 0.3, 0.4, 0.5, 0.6 or a range value between any two of them.

[0062] The molar ratio of the water to the silicon source I is 25 to 60;

[0063] Optionally, the molar ratio of the water to the silicon source I is any value among 25, 30, 40, 50, 60 or a range between any two of them.

[0064] The molar ratio of the organic additive to the silicon source I is 0.02 to 0.4;

[0065] Optionally, the molar ratio of the organic additive to the silicon source I is any value among 0.02, 0.05, 0.1, 0.2, 0.3, 0.4 or a range value between any two of them.

[0066] The molar amount of the silicon source I is calculated based on the molar amount of SiO2 in the selected silicon source I;

[0067] The molar amount of the aluminum source I is calculated based on the molar amount of Al2O3 in the selected aluminum source I;

[0068] The molar amount of the inorganic base I is calculated based on the molar amount of the hydroxide in the selected inorganic base I.

[0069] The temperature of the aging I is 25-80° C.;

[0070] Optionally, the temperature of the aging I is any value of 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, or any range therebetween.

[0071] The aging time is 2 to 8 hours;

[0072] Optionally, the aging time I is any value among 2h, 3h, 4h, 5h, 6h, 7h, 8h, or a range value between any two of them.

[0073] The temperature of the crystallization I is 140-200° C.;

[0074] Optionally, the temperature of the crystallization I is any value among 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, or any range between any two of them.

[0075] The crystallization time I is 48 to 125 hours.

[0076] Optionally, the crystallization time I is any value among 48h, 50h, 75h, 100h, 125h, or a range value between any two of them.

[0077] The crystallization I is a hydrothermal dynamic crystallization, which is carried out in a kettle reactor in a rotary oven, and the rotating speed of the rotary oven is 10 to 80 r / min.

[0078] According to another aspect of the present application, there is provided an application of the above-mentioned xylene isomerization molecular sieve catalyst for xylene isomerization reaction.

[0079] The following steps are involved:

[0080] contacting a raw material containing xylene with the xylene isomerization molecular sieve catalyst to react;

[0081] The reaction temperature is 250-450°C;

[0082] The reaction pressure is 0-2MPa;

[0083] The reaction space velocity is 1 to 30 h -1 .

[0084] The beneficial effects of this application are:

[0085] (1) The ZSM-48 molecular sieve in the xylene isomerization molecular sieve catalyst described in the present application has a large number of mesopores, which significantly improves the diffusion performance of the one-dimensional pore molecular sieve, which will help to improve the catalytic stability of the catalyst.

[0086] (2) The ZSM-48 molecular sieve in the xylene isomerization molecular sieve catalyst described in the present application has a larger adjustable range of silicon-aluminum ratio and its acidity is significantly improved compared with the traditional ZSM-48, which will help to improve the catalytic activity of the catalyst.

[0087] (3) The method used in this application is a one-step hydrothermal crystallization method, and no complex organic additives are used, so the preparation process is simple and economical. BRIEF DESCRIPTION OF THE DRAWINGS

[0088] Figure 1 X-ray diffraction (XRD) patterns of samples prepared in Examples 1 to 5.

[0089] Figure 2This is a scanning electron microscope (SEM) image of the sample prepared in Example 1, with a scale of 100 nm. DETAILED DESCRIPTION

[0090] The present invention is further described below with examples, but the examples are not intended to limit the present invention.

[0091] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0092] The specific information of various substances used in the examples are as follows:

[0093] Silica sol (Qingdao Ocean Chemical Co., Ltd., 30wt% SiO2);

[0094] White carbon (McLean, 95wt% SiO2);

[0095] Tetraethyl orthosilicate (TEOS) (Kermel, >98wt%);

[0096] Al2(SO4)3·18H2O (Sinopharm Group, 98wt%);

[0097] Al(NO3)3·9H2O (Sinopharm Group, 99wt%);

[0098] Pseudoboehmite (McLean, 66%wtAl2O3, 33wt%H2O);

[0099] NaOH (Sinopharm Group, >96wt%);

[0100] KOH (Kermel, 85 wt%);

[0101] HMBr (Aladdin, 98 wt%);

[0102] HMCl (Aladdin, 98wt%)

[0103] TEACl (Aladdin, 99 wt %);

[0104] TEABr (Aladdin, 99 wt %);

[0105] TMAF (McLean 97wt%);

[0106] NaOH (Sinopharm Group, >96wt%);

[0107] HDA (Sinopharm Group, analytical grade);

[0108] Meta-xylene (Aladdin, 99.9wt%)

[0109] High-purity nitrogen (Dalian Institute of Chemical Physics, 99.9wt%)

[0110] Al2O3 (Sinopharm Group, analytical grade)

[0111] Deionized water (homemade).

[0112] Preparation Example 1:

[0113] Preparation of ZSM-48 molecular sieve seed crystals:

[0114] Under stirring conditions, 0.30g Al2(SO4)3·18H2O, 5.80g HDA, 0.30g NaOH, and 3.50g TEABr were dissolved in 43.70g deionized water. After complete dissolution, 21.80g silica sol was added dropwise under stirring conditions to prepare an initial sol. The initial sol was stirred and aged at 45°C for 4h, transferred to a stainless steel reactor, placed in a rotary oven, and hydrothermally crystallized at 160°C and 60r / min for 72h. After the crystallization was completed, it was cooled to room temperature with cold water, filtered, washed, and dried to obtain ZSM-48 molecular sieve seed crystals.

[0115] Preparation Example 2:

[0116] Preparation of ZSM-48 molecular sieve seed crystals:

[0117] Under stirring conditions, 0.22g NaOH, 3.10g HDA, 0.062g Al(NO3)3·9H2O, and 1.50g TMAF were dissolved in 60.00g deionized water, and 4.20g white carbon black was added under stirring conditions. After stirring evenly, the initial gel was aged at 40°C for 2h, transferred to a stainless steel reactor, placed in a rotary oven, and hydrothermally crystallized at 180°C and 60r / min for 60h. After the crystallization, it was quenched to room temperature with cold water, filtered, washed, and dried to obtain ZSM-48 molecular sieve seed crystals.

[0118] Example 1

[0119] Under stirring conditions, 0.88g Al2(SO4)3·18H2O, 1.01g HMBr, and 0.78g NaOH were dissolved in 37.29g H2O. After complete dissolution, 0.30g of the seed obtained in Preparation Example 1 was added under stirring conditions, and then 18.26g silica sol was added dropwise. The initial gel was stirred and aged at 45°C for 4h, transferred to a stainless steel reactor, placed in a rotary oven, and hydrothermally crystallized at 160°C and 60r / min for 36h. After the crystallization was completed, it was quenched to room temperature with cold water, filtered, washed, and dried to obtain the sodium-type molecular sieve raw powder.

[0120] The XRD pattern of the obtained product is as follows Figure 1 As shown, it is a pure phase ZSM-48 molecular sieve. Figure 2It can be seen that the product is in the form of short rod stacking.

[0121] The silicon-to-aluminum ratio of the product was determined to be 55 by XRF.

[0122] The micropore volume of the product was determined to be 0.076 cm by N2 adsorption-desorption characterization. 3 / g, and the mesopore volume is 0.74cm 3 / g.

[0123] Example 2

[0124] Under stirring conditions, 0.85g Al(NO3)3·9H2O, 0.77g HMCl, and 1.12g NaOH were dissolved in 50g H2O. After complete dissolution, 0.88g of the seed crystal obtained in Preparation Example 1 was added under stirring conditions, and then 5.84g of white carbon black was slowly added. The initial gel was stirred and aged at 60°C for 2h, transferred to a stainless steel reactor, placed in a rotary oven, and hydrothermally crystallized at 160°C and 60r / min for 36h. After the crystallization was completed, it was quenched to room temperature with cold water, filtered, washed, and dried to obtain the sodium type molecular sieve raw powder.

[0125] The XRD pattern of the obtained product is as follows Figure 1 As shown, it is a pure phase ZSM-48 molecular sieve; the electron microscopy results show that the product has a short rod stacking morphology.

[0126] The silicon-to-aluminum ratio of the product was determined to be 62 by XRF.

[0127] The micropore volume of the product was determined by N2 adsorption-desorption characterization to be 0.072 cm 3 / g, and the mesopore volume is 0.68cm 3 / g.

[0128] Example 3

[0129] Under stirring conditions, 0.15g pseudo-boehmite and 1.44g HMCl were dissolved in 30.00g H2O, and the solution was recorded as solution A after complete dissolution. 1.28g KOH was dissolved in 20g water, and then 19.26g TEOS was added to hydrolyze at 40°C for 4h, and then solution A was added dropwise, and then 0.40g of the seed obtained in Preparation Example 2 was added to prepare the initial gel. The initial gel was stirred and aged at 60°C for 2h, transferred to a stainless steel reactor, placed in a rotary oven, and hydrothermally crystallized at 160°C and 60r / min for 24h. After the crystallization was completed, it was quenched to room temperature with cold water, filtered, washed, and dried to obtain the sodium-type molecular sieve raw powder.

[0130] The XRD pattern of the obtained product is as follows Figure 1 As shown, it is a pure phase ZSM-48 molecular sieve; the electron microscopy results show that the product has a short rod stacking morphology.

[0131] The silicon-to-aluminum ratio of the product was determined to be 50 by XRF.

[0132] The micropore volume of the product was determined by N2 adsorption-desorption characterization to be 0.080 cm 3 / g, and the mesopore volume is 0.78cm 3 / g.

[0133] Example 4

[0134] Under stirring conditions, 3.08g HMOH, 0.20g NaOH, and 0.51g Al2(SO4)3·18H2O were dissolved in 50g H2O. After complete dissolution, 1.20g of the seed crystals obtained in Preparation Example 1 were added under stirring conditions, and then 5.84g of white carbon black was slowly added. The initial gel was stirred and aged at 40°C for 4h, transferred to a stainless steel reactor, placed in a rotary oven, and hydrothermally crystallized at 150°C and 60r / min for 96h. After the crystallization was completed, it was quenched to room temperature with cold water, filtered, washed, and dried to obtain the sodium-type molecular sieve raw powder.

[0135] The XRD pattern of the obtained product is as follows Figure 1 As shown, it is a pure phase ZSM-48 molecular sieve; the electron microscopy results show that the product has a short rod stacking morphology.

[0136] The silicon-to-aluminum ratio of the product was determined to be 102 by XRF.

[0137] The micropore volume of the product was determined by N2 adsorption-desorption characterization to be 0.070 cm 3 / g, and the mesopore volume is 0.55cm 3 / g.

[0138] Example 5

[0139] Under stirring conditions, 2.02g HMBr, 1.56g NaOH, and 0.85g Al2(SO4)3·18H2O were dissolved in 37.29g H2O. After complete dissolution, 0.50g of the seed crystal obtained in Preparation Example 2 was added under stirring conditions, and then 18.26g silica sol was added dropwise. The initial gel was stirred and aged at 40°C for 4h, transferred to a stainless steel reactor, placed in a rotary oven, and hydrothermally crystallized at 170°C and 60r / min for 20h. After the crystallization was completed, it was quenched to room temperature with cold water, filtered, washed, and dried to obtain the sodium-type molecular sieve raw powder.

[0140] The XRD pattern of the obtained product is as follows Figure 1 As shown, it is a pure phase ZSM-48 molecular sieve; the electron microscopy results show that the product has a short rod stacking morphology.

[0141] The silicon-to-aluminum ratio of the product was determined to be 40 by XRF.

[0142] The micropore volume of the product was determined to be 0.077 cm by N2 adsorption-desorption characterization. 3 / g, and the mesopore volume is 0.80cm 3 / g.

[0143] Catalytic performance verification:

[0144] The molecular sieves obtained in Examples 1 to 5 were subjected to ion exchange and calcination to obtain hydrogen-type ZSM-48 molecular sieves. The ion exchange procedure is that the molecular sieve powder is added to a 1 mol / L NH4Cl or NH4NO3 solution at a water-powder mass ratio of 15, and ion exchange is performed at 80°C for 4 hours. The calcination procedure is calcined at 520°C for 3 hours in an air atmosphere. The molecular sieve products obtained in Examples 1 to 3 are formed by tableting and crushed into 20-40 mesh particles for standby use. The molecular sieve products obtained in Examples 4 to 5 are formed by extrusion, the binder is Al2O3, the molecular sieve content is 85%, and the catalyst is crushed into 20-40 mesh particles for standby use after drying. The catalytic performance of the catalyst is evaluated and tested by the isomerization reaction of meta-xylene. The reactant raw material is 99.9wt% meta-xylene. Before the reaction, the catalyst is activated at 500°C for 2 hours in a nitrogen atmosphere at normal pressure. After the temperature dropped to 400°C, the pressure was adjusted to 0.5 MPa, and then m-xylene was introduced into the reaction system using a double plunger pump to start the reaction. During the reaction, the molar ratio of nitrogen to m-xylene was maintained at 300. The mass space velocity of m-xylene was 18 h -1 .

[0145] After 24 hours of reaction, samples were collected for analysis, which was recorded as product I; after 96 hours of reaction, samples were collected for analysis, which was recorded as product II. The results are shown in Table 1.

[0146] Table 1 Catalytic performance of catalysts in Examples 1 to 5

[0147]

[0148] It can be seen from Table 1 that the catalyst prepared according to the present invention has good catalytic activity, para-xylene selectivity and catalytic stability.

[0149] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A xylene isomerization molecular sieve catalyst, characterized in that: The xylene isomerization molecular sieve catalyst comprises an aluminum-rich multi-level pore hydrogen-type ZSM-48 molecular sieve with a short rod-like stacking morphology and a binder; The mass content of the aluminum-rich multi-level pore hydrogen-type ZSM-48 molecular sieve in the xylene isomerization molecular sieve catalyst is 40 to 90 wt %; The silicon-aluminum ratio of the aluminum-rich multi-level pore hydrogen-type ZSM-48 molecular sieve is 400 to 200; The micropore volume of the aluminum-rich multi-level pore hydrogen-type ZSM-48 molecular sieve is 0.04 to 0.09 cm 3 / g; The mesopore volume of the aluminum-rich multi-level pore hydrogen-type ZSM-48 molecular sieve is 0.2 to 0.8 cm 3 / g; The binder is selected from at least one of alumina, silica and clay.

2. A method for preparing a xylene isomerization molecular sieve catalyst according to claim 1, characterized in that: The following steps are involved: The raw materials containing silicon source, aluminum source, inorganic base, template agent, seed crystal and water are placed in a sealed container for aging, crystallization, ion exchange, roasting and molding to obtain the xylene isomerization molecular sieve catalyst.

3. The preparation method according to claim 2, characterized in that: The silicon source is selected from at least one of white carbon black, silica sol, ethyl orthosilicate and water glass; The aluminum source is selected from at least one of aluminum nitrate, aluminum sulfate, sodium aluminate, pseudo-boehmite, and aluminum chloride; The inorganic base is selected from at least one of sodium hydroxide, sodium carbonate, potassium hydroxide, lithium hydroxide and ammonia water; The template agent is at least one of hexamethylammonium bromide, hexamethylammonium chloride and hexamethylammonium hydroxide.

4. The preparation method according to claim 2, characterized in that: The molar ratio of the inorganic base to the silicon source is 0.2 to 0.6; The molar ratio of the silicon source to the aluminum source is 60 to 250; The molar ratio of the template to the silicon source is 0.02 to 0.3; The molar ratio of the water to the silicon source is 25 to 60; The mass ratio of the seed crystal to SiO2 in the silicon source is 1% to 20%; The molar amount of the silicon source is calculated based on the molar amount of SiO2 in the selected silicon source; The molar amount of the aluminum source is calculated based on the molar amount of Al2O3 in the selected aluminum source; The molar amount of the template is calculated based on the molar amount of hexamethylammonium ions in the selected template; The molar amount of the inorganic base is calculated based on the molar amount of the hydroxide in the selected inorganic base.

5. The preparation method according to claim 2, characterized in that: The aging temperature is 25 to 80° C. The aging time is 2 to 8 hours. The crystallization temperature is 140-200°C. The crystallization time is 12 to 120 hours. Preferably, the crystallization is hydrothermal dynamic crystallization, which is carried out in a kettle reactor in a rotary oven, and the rotation speed of the rotary oven is 10 to 80 r / min.

6. The preparation method according to claim 2, characterized in that: The seed crystal is a ZSM-48 seed crystal; The ZSM-48 seed crystals are obtained by the following process: The raw materials containing silicon source I, aluminum source I, inorganic base I, template agent I, organic additive and water are aged I, crystallized I and dried in a closed container to obtain the ZSM-48 seed crystal; The silicon source I is selected from at least one of white carbon black, silica sol, ethyl orthosilicate, and water glass; The aluminum source I used is at least one of aluminum nitrate, aluminum sulfate, sodium aluminate, pseudo-boehmite, and aluminum chloride; The template agent I is selected from 1,6-hexanediamine; The inorganic base I is selected from at least one of sodium hydroxide, sodium carbonate, potassium hydroxide, lithium hydroxide and ammonia water; The organic additive is selected from at least one of tetramethylammonium hydroxide, tetramethylammonium chloride, tetramethylammonium bromide, tetramethylammonium fluoride, tetraethylammonium bromide, tetraethylammonium chloride, tetraethylammonium hydroxide and tetraethylammonium fluoride.

7. The preparation method according to claim 6, characterized in that: The molar ratio of the silicon source I to the aluminum source I is at least 200; The molar ratio of the inorganic base I to the silicon source I is 0.03 to 0.2; The molar ratio of the template agent I to the silicon source I is 0.2 to 0.6; The molar ratio of the water to the silicon source I is 25 to 60; The molar ratio of the organic additive to the silicon source I is 0.02 to 0.4; The molar amount of the silicon source I is calculated based on the molar amount of SiO2 in the selected silicon source I; The molar amount of the aluminum source I is calculated based on the molar amount of Al2O3 in the selected aluminum source I; The molar amount of the inorganic base I is calculated based on the molar amount of the hydroxide in the selected inorganic base I.

8. The preparation method according to claim 6, characterized in that: The temperature of the aging I is 25-80° C.; The aging time is 2 to 8 hours; The temperature of the crystallization I is 140-200° C.; The crystallization time I is 48 to 125 hours. The crystallization I is a hydrothermal dynamic crystallization, which is carried out in a kettle reactor in a rotary oven, and the rotating speed of the rotary oven is 10 to 80 r / min.

9. An application of the xylene isomerization molecular sieve catalyst according to claim 1, characterized in that: Used for xylene isomerization reaction.

10. The use according to claim 9, characterized in that: The following steps are involved: contacting a raw material containing xylene with the xylene isomerization molecular sieve catalyst to react; The reaction temperature is 250-450°C; The reaction pressure is 0-2MPa; The reaction space velocity is 1 to 30 h -1 .